Dampak Kebutuhan Hunian Mahasiswa Pada Zona Permukiman (Studi Kasus: Gampong Lamgugob, Kecamatan Syiah Kuala, Kota Banda Aceh) - Syiya Minta; Putra Rizkiya; Zahrul Fuady (Universitas Syiah Kuala, 2022)
The existence of public and private universities in Banda Aceh city causes an increasing number of students coming from other cities to the city of Banda Aceh. These students are referred to as student migrants. The large number of student migrants affects the demand for student housing. The demand for student housing encourages people to build rental and indekos houses. In addition to rental houses and indekos, some students also live in dormitories. Gampong Lamgugob is one of the gampong that has the availability of student housing. This research aims to find out the availability of student housing in Lamgugob gampong and the impact of student occupancy availability on changes in settlement activities. Data collection techniques are field surveys, in-depth interviews and documentation studies. The data analysis technique used is a qualitative descriptive analysis technique to explain the availability of student housing and the impact of student occupancy availability on changes in settlement activities. Based on research, the availability of student housing in Gampong Lamgugob amounted to 131 dwellings which included 51 indekos, 76 rental houses and 4 dormitories with a total number of 1,121 students. The fulfillment of student occupancy needs is also accompanied by the provision of supporting facilities for student needs. The provision of student housing and supporting facilities for student needs led to changes in settlement activities. The settlement activities in question are the change of community occupancy into student occupancy and service trade activities. The change of community housing activities to student housing amounted to 25 housing units and the change of community houses into service trade activities amounted to 23 housing units.